2022
DOI: 10.12688/f1000research.75703.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the knowledge, attitudes and practices of Lebanese shoppers towards food labeling: The first steps in the Nutri-score roadmap

Abstract: Background: Food labeling is a fundamental educational tool for advocating for public awareness. It emphasizes knowledge of the nutrient content of food and thus directs the choice towards the healthiest food products. This cross-sectional survey aimed to assess the knowledge, attitudes, and practices (KAP) regarding nutrition label use in Lebanon through a valid questionnaire. Methods: Overall, 768 participants (mean age: 30.8 ±12, males: 60.2%) were recruited randomly between February and May 2020. We used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…This is in accordance with the research conducted by Vania Candra et al 24 , which showed that there was a significant relationship between the respondents level of knowledge about reading packaged food labels and the practice of choosing packaged food, where respondents with very good knowledge will practice good packaged food selection. This is also supported by research conducted by Maha Hoteit et al 25 , where there is a positive relationship between knowledge and buyer behaviour in Lebanon in reading packaged food labels when buying packaged food.…”
Section: Discussionsupporting
confidence: 68%
“…This is in accordance with the research conducted by Vania Candra et al 24 , which showed that there was a significant relationship between the respondents level of knowledge about reading packaged food labels and the practice of choosing packaged food, where respondents with very good knowledge will practice good packaged food selection. This is also supported by research conducted by Maha Hoteit et al 25 , where there is a positive relationship between knowledge and buyer behaviour in Lebanon in reading packaged food labels when buying packaged food.…”
Section: Discussionsupporting
confidence: 68%
“…One possible explanation for observing such findings in the MENA countries is that this concept and its application have neither been entered into school curricula and textbooks nor in education programs, to empower individuals in basing their food choices according to nutrition- and safety-related considerations. One recent study showed that Lebanese shoppers expressed poor nutrition-label-related knowledge, and more than half the population either read nutrition labels occasionally or did not look at the food label at all [ 82 ]. Emirati consumers reported looking mostly at the expiration date of the products rather than the information related to the food-storage and -handling instructions and the biotechnology as well, which are key components of being food literate [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Food-literacy interventions focusing on consumer’ skills to read food labels should be prioritized in such regions, where nutrition inadequacy and malnutrition are not uncommon. Thereupon, Hoteit M. and colleagues (2022) [ 82 ] provided data on this topic, “the first steps in the Nutri-Score roadmap”, to serve as an initiative to motivate the national implementation of food-labeling approaches in Lebanon such as the Nutri-Score front-of-pack label.…”
Section: Resultsmentioning
confidence: 99%
“…As for data on KAB, this information was available in 10 EMR countries (45%), including Bahrain, Egypt, Iran, Jordan, KSA, Kuwait, Lebanon, Morocco, Oman and Pakistan. The majority of KAB surveys included questions related to (1) knowledge of sugar food sources, sugar content in food products, and familiarity with adverse weight/health effects of high sugar intakes; (2) consumer’s attitude such as importance of restricting/limiting the intake of sugar, making healthier choices and checking information related to sugar; and (3) consumers’ behavior such as consuming high sugar food products, reducing the amount of AS, substituting high-sugar options with healthier options and reading labels ( Table S7 ) [ 72 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. Poor knowledge related to sugar food sources and content was reported from more than 65% of school-aged children in Jazan, KSA [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 77.5% of male schoolchildren in Riyadh, KSA [ 100 ], 61% of college students in Muscat, Oman [ 107 ] and 85% of adults in Rawalpindi cantonment in Pakistan [ 111 ], were unaware of the adverse health effects of high sugar consumption. A national study in Lebanon showed that less than 50% of adolescents and adults did not know what a “sugar-free” claim indicates [ 116 ]. As for attitude, more than 80% of schoolchildren in Jazan, KSA preferred high sugar foods and beverages, as compared to healthier options [ 98 ].…”
Section: Resultsmentioning
confidence: 99%